A novel approach to reduce in-service temperature in WC-Co cutting tools. Issue 3 (15th February 2020) - Guimarães, B.; Fernandes, C.M.; Figueiredo, D.; Cerqueira, M.F.; Carvalho, O.; Silva, F.S.; Miranda, G.
Abstract: The high temperatures generated in the cutting zone during machining processes results in an increase of wear mechanisms, reducing the lifetime of cutting tools. In this sense, cutting tools industry is constantly looking for new ways to reduce this temperature. This work proposes a novel cemented carbide cutting tool design and fabrication process for enhancing these tools thermal conductivity. This design incorporates copper heat sinks in designated strategic locations, fabricated using innovative laser green compacts machining. A thermal conductivity of 127 W/m.K was obtained for WC-Co/Cu, considerably higher than that of WC-Co (36 W/m.K). This approach for obtaining WC-Co/Cu cutting tools was found effective for increasing locally the thermal conductivity, especially in the cutting zone vicinity.